Investigating the Impact of Corporate Governance mechanisms on Financial Performance in Financial Reports in Iraq - Naser Jasim Alghaith, Haitham; Dastgir, Mohsen; Hamza Habeeb Almagtome, Akeel; Ali Ahmadi, Saeid (Business, Marketing, and Finance Open, 2026)
The aim of this study was to investigate the effect of corporate governance mechanisms on financial performance in companies listed on the Iraqi Stock Exchange. In the present study, data related to testing the research hypotheses were collected by referring to the Central Bank of Iraq and the audited financial statements of companies listed on the Baghdad Stock Exchange and referring to the website www.isx-iq.net. The statistical population of this study was all companies listed on the Baghdad Stock Exchange in the period 2016-2021. The systematic elimination method was used for sampling. The statistical analysis was carried out to estimate the research model using multiple regression, which used Excell and Eviews software in this regard, and the models were estimated using random and fixed effects of panel data and ordinary least squares methods. Using data from listed companies for the country of Iraq, the first to sixth hypotheses are confirmed. The results showed that, in accordance with the theoretical foundations, the percentage of institutional shareholders, board independence and internal audit effectiveness have a positive and significant effect on performance. However, CEO ambivalence reduces performance.